What Holds Europe Together? - Krzysztof Michalski (Central European University Press, 2005)
The book addresses contemporary developments in European identity politics as part of a larger historical trajectory of a common European identity based on the idea of 'solidarity.' The authors explain the special sense in which Europeans perceive their obligations to their less fortunate compatriots, to the new East European members, and to the world at large. An understanding of this notion of 'solidarity' is critical to understanding the specific European commitment to social justice and e...